Adaptação cultural e validação do "Work related activities that may contribute to job-related pain and/or injury" para a lingua portuguesa do Brasil - Coluci, Marina Zambon Orpinelli, 1982- (2008)
Orientador: Neusa Maria Costa Alexandre